Training and International Exhibitions: Building the Competitiveness of MSMEs through Increasing Productivity - Iskandarsyah; Halim, Hendra; Faisal; Darwanis; Murkhana; Noor Azuddin Yakob; M. Shabri Abdul Majid; Taufiq C. Dawood; Muhammad Adam; Amri; Mirna Indriani; Muhammad Haris Riyaldi (IJCS: International Journal of Community Service, 2023)
This community service initiative by the Faculty of Economics and Business, Syiah Kuala University, aimed to enhance the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) owned by university students. Utilizing the Service Learning method, the program focused on improving operational efficiency through training in time management, inventory control, product quality enhancement, and technology application. The initiative culminated in an international product exhibition at Universiti Kebangsaan Malaysia, providing MSMEs with opportunities for global market exposure. Post-evaluation demonstrated a significant increase in productivity among participants, evidenced by improved time management and product quality. The project's success highlights the positive impact of holistic approaches that integrate training and international marketing efforts on local economies. Future initiatives should explore deeper aspects like innovation and advanced marketing strategies for sustained MSME growth